Enlisting Employees in Improving Payroll-Tax Compliance: Evidence from Mexico - Todd J. Kumler; Eric Verhoogen; Judith A. Frias (Institute for the Study of Labor (IZA), 2013)
Non-compliance of firms with tax regulations is a major constraint on state capacity in developing countries. We focus on an arguably under-appreciated dimension of non-compliance: under-reporting of wages by formal firms to evade payroll taxes. We develop a simple partial-equilibrium model of endogenous compliance by heterogeneous firms to guide the empirical investigation. We then compare two independent sources of individual-level wage information from Mexico firms' wage reports to the Mexican social security agency and workers' responses to a household labor-force survey to investigate the extent of wage under-reporting and how it responded to an important change in the social security system. We document that under-reporting by formal firms is extensive, and that compliance is better in larger firms. Using a difference-in-differences strategy based on the 1997 Mexican pension reform, which effectively tied pension benefits more closely to reported wages for younger workers than for older workers, we show that the reform led to a relative decline in under-reporting for younger workers. Within metro area/sector/firm size cells, the decline in under-reporting was greater in cells initially employing a younger workforce on average. The empirical patterns are consistent with our theoretical model and suggest that giving employees incentives and information to improve the accuracy of employer reports can be an effective way to improve payroll-tax compliance.
Keywords: O17; H26; H55; 330; tax compliance; state capacity; Mexico; heterogeneous firms; pension reform; Lohnsteuer; Steuermoral; Unternehmen; Gesetzliche Rentenversicherung; Datenerhebung; Mexiko; Entwicklungsländer